SISTEM PENGENDALIAN PEMBIAYAAN MURABAHAH PADA PT. BPRS LAMPUNG TIMUR - Moh Abdur Rohman Wahid (EKSYDA: Jurnal Studi Ekonomi Syariah, 2020)
This research is a qualitative research. The methods used are documentation and interview methods. The analysis carried out is that the data is obtained, collected, processed, analyzed, adjusted between the concept and application of the Murabahah financing control system at the BPRS, interpretation and review then conclusions are drawn. In addition, this research also conducts a SWOT analysis on Murabahah Financing, then the authors make a strategy design in order to increase Murabahah Financing in managing the distribution of financing to BPRS. The results showed that the existing control activities at the BPRS were not guided by written controls but were based on directions and directives from the board of directors or commissioners. The control system is reflected in the organizational structure of the financing, financing systems and procedures, and efforts at guidance and supervision. The objective of the financing control carried out by the BPRS is to manage existing financing so that it remains smooth and productive. Based on the SWOT analysis of Murabahah Financing, when viewed from the SWOT, it is found that the SO, ST, WO, WT strategies, the need to build relationships with other parties and perform symmetric information about the advantages of buying and selling products. Adjusting products with competitors' products, so that they can serve customers effectively and efficiently.